The Big Sell: Privatizing East Germany's Economy - Lukas Mergele; Moritz Hennicke; Moritz Lubczyk (Center for Economic Studies and Ifo Institute (CESifo), 2020)
The end of communism in the 1990s probably is the most fundamental restructuring of institutions witnessed in recent history. At its core was the large-scale redistribution of previously state-owned companies. We construct a unique firm-level dataset to study this redistribution in East Germany where the entire state-owned economy was either privatized or liquidated within less than five years. We examine whether the privatization authority followed its mandate to privatize competitive firms using initial labor productivity to indicate firms' competitiveness. Our results highlight that firms with higher baseline productivity are more likely to be privatized, yield higher sales prices, are more often acquired by West German investors, and are more likely to remain in business even 20 years after leaving public ownership. The privatization agency plausibly contributed to these outcomes by rating and prioritizing productive firms.
Keywords: D24; G38; H11; L33; P31; 330; privatization; labor productivity; German reunification